Optimalisasi Prediksi Klaim Kendaraan Bermotor Menggunakan Time Series Analysis dengan Pendekatan Variasi Kalender dalam Perusahaan Asuransi Umum - Gede Rama Darma Wijaya; R. Mohamad Atok (Universitas Methodist Indonesia, 2026)
General insurance companies face significant challenges in predicting motor vehicle insurance claims due to seasonal fluctuations and calendar variations. This study aims to optimize the accuracy of claim predictions using the Autoregressive Integrated Moving Average (ARIMA) method combined with a calendar variation approach. Data analysed includes nominal claim values from January 2015 to December 2023. Regression analysis results show that calendar variations, specifically periods